Las rupturas de Concha Méndez en Inquietudes, Surtidor y Canciones de mar y tierra - Piña Laynes, Alma Alicia (Romanica Silesiana)
This paper provides an analysis of the early work of Concha Méndez (Spain, 1898—1986). Unfortunately, and due to a gender bias, her work has been neglected in most literary studies. The main claim of the following analysis is that the writing in her three early books reflects a rupture at both the personal and poetic level, in an attempt to make her work a part of the Spanish literary horizon of that time. Méndez disrupts the status quo: she is not a tearful and confessional poet, but rather one who puts forward a gynocentrist view in her poems. Furthermore, and unlike the average female poet, she chose to use an avant-garde style. In doing so, Méndez became a leader in promoting female freedom and in socially constructing the image of the new woman. Key words: Gynocentrist view, vanguard, social construction of image.